Impact of Training on Knowledge of Rural Women Regarding Appropriate Child Care Practices - Vinita Singh , K. S. Yadav; Vivekin Pachauri (Indian Journal of Extension Education, 2017)
The present study was conducted in the Chitora and Baroda villages of Sagar district with selection of 62 women of age group 18-40 years as respondents. The objective was to find out the impact of KVK training on their knowledge about appropriate child care practices. To collect data, a pre-structured interview schedule was used. Result of the study revealed that the knowledge level of women significantly increased after imparting the training programme. The mean pre-training knowledge score was 2.70±1.45 which increased up to 4.42±1.01 after the training. It has also been found that the knowledge of women regarding child care was significantly correlated with the type of family, income, education and exposure to mass media.